Listener perceptions of simulated fluent speech in nonfluent aphasia. Issue 8 (2nd August 2016) - Harmon, Tyson G.; Jacks, Adam; Haley, Katarina L.; Faldowski, Richard A.
Abstract : Background : People with aphasia (PWA) are frequently perceived less favourably by listeners than their peers. These perceptions include incorrect assumptions that can prevent successful social interactions. While communication partner training has been shown to improve social outcomes related to the listener, changing the verbal output of PWA may also yield more favourable listener perceptions about the speech, speaker, and their own affective response. We investigated the effects of artificially altered fluency (i.e., simulated fluency) on listeners' subjective impressions. Aims : The purpose of the study was to (1) confirm that listeners perceive PWA less favourably than their neurologically healthy peers and (2) determine the effects of simulated fluency on listener perceptions about PWA. Methods & Procedures : Thirty-eight listeners heard nine narrative monologue language samples from three conditions (i.e., speakers with nonfluent aphasia, simulated fluent samples from the same speakers, and neurologically healthy speakers). Listeners responded to a nine-item questionnaire that probed perceptions about speech output, speaker attributes, and listener feelings. Outcomes & Results : Listeners perceived PWA less favourably than their neurologically healthy peers. Simulated fluency yielded more positive listener perceptions for all questionnaire items except speech intelligibility, which was unchanged by simulated fluency. Conclusions : Simulated fluency improved listener perceptions of PWA significantly, indicating that speech fluency may be a socially valid treatment target in aphasia. Beyond direct training of communication partners, changing the verbal output of aphasic speech can also yield more positive listener perceptions of PWA.